2021
DOI: 10.1007/s00246-021-02651-9
|View full text |Cite
|
Sign up to set email alerts
|

Multisystem Inflammatory Syndrome Associated with COVID-19 Anti-thrombosis Guideline of Care for Children by Action

Abstract: With growing number of pediatric cases of COVID-19, a unique hyper-inflammatory syndrome, linked to SARS-CoV-2 infection, has emerged in children referred to as multisystem inflammatory syndrome in children (MIS-C). This Kawasaki Disease (KD)-like illness has been described across the world. This syndrome shares features of KD, toxic shock syndrome, and macrophage activation syndrome and is associated with significantly elevated inflammatory markers. Everyday there are new data emerging improving the care of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 15 publications
0
21
0
Order By: Relevance
“…We terminated the treatment of the patient who did not have dimer elevation or signs of thrombosis in the control. Guidelines regarding the thrombotic evaluation and anticoagulation management of hospitalized children with MIS-C remains lacking [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…We terminated the treatment of the patient who did not have dimer elevation or signs of thrombosis in the control. Guidelines regarding the thrombotic evaluation and anticoagulation management of hospitalized children with MIS-C remains lacking [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…One study showed that initial therapy with a combination of IVIG and corticosteroids is superior at reducing cardiovascular dysfunction and vasodilatory shock, while a second study revealed no difference in initial therapies on cardiovascular outcomes [26 Thrombotic complications are common with MIS-C, and patients with thrombotic complications have higher mortality [59]. In patients with greater than mild to moderate levels of depressed ventricular function, anti-coagulation with heparin, enoxaparin, warfarin, and/or anti-platelet agents should be considered to prevent intra-cardiac thrombi and subsequent embolic events [60]. Patients with giant coronary artery aneurysms also require aggressive anti-coagulation, initially with heparin or enoxaparin with subsequent later conversion to a regimen of warfarin and anti-platelet agents [61].…”
Section: Management Of Mis-cmentioning
confidence: 99%
“…In mild to moderate cases of MIS-C, it should use prophylactic doses of enoxaparin (0.5 mg/kg every 12 h), and in severe cases, therapeutic doses may be used. 10,24,25 In addition, supportive interventions such as early respiratory support for patients with respiratory failure, adequate fluid resuscitation, and vasopressor support for patients with shock also play an important role.…”
Section: Discussionmentioning
confidence: 99%